'Got to gamble, but I've got no money.' A qualitative analysis of gambling careers in South Italy. Issue 1 (2nd January 2019) - Rolando, Sara; Beccaria, Franca
ABSTRACT: With its geographical differences, Italy provides an interesting case study for analysing the cultural and contextual origin of gambling-related problems. By investigating gambling careers, the study sought to scrutinize the interplay between the personal and environmental factors – including social and cultural aspects – that influence changes in gambling habits among gamblers in Naples (South Italy). The convenience sample consisted of 42 problem and recreational gamblers, male and female, aged between 23 and 71 years, with different employment status and educational level. Results clarify how Neapolitans' gambling habits have moved towards individualization over time, how availability contributes to increasing gambling in various ways, and how employment status and concerns about money can increase the risk of gambling-related problems, thereby increasing socio-economic inequalities. Confirming previous studies, the study casts doubt on the idea that problem gambling is a chronic and progressive disease, and suggests that periods of excessive gambling can be followed by periods of regulated activity, even without turning to formal treatment. However, life events – either positive or negative – can hinder attempts to regulate gambling.